Indian Ocean as a New Political and Security Region - Hamna Ghias Sheikh (CISS Insight Journal, 2024)
The book Indian Ocean as a New Political and Security Region by Frédéric Grare and Jean-Loup Samaan offers a comprehensive analysis of the Indian Ocean’s transformation into a pivotal geopolitical and security arena. Grare, a Senior Policy Fellow at the European Council on Foreign Relations (ECFR) and a non-resident senior fellow at the Carnegie Endowment for International Peace, along with Samaan, a Senior Research Fellow at the Middle East Institute of the National University of Singapore and Associate Researcher with the French Institute of International Relations, bring their extensive expertise to this study. This comprehensive work moves beyond the historical role of the Indian Ocean as a maritime trade route to examine its emerging status as a strategic hub. The central theme of the Indian Ocean as a New Political and Security Region is the transformation of the Indian Ocean Region (IOR) into a pivotal geopolitical and security arena. The book explores the evolving strategic dynamics in the region, driven by the intersecting interests of major global powers, emerging regional actors, and shifting economic and security landscapes. It emphasizes the growing competition for influence among global and regional powers like the United States, China, and India, while also examining the roles of European states, Gulf Arab monarchies, Association of Southeast Asian Nations (ASEAN) countries, Australia, and Africa